Signatures of selection in core and accessory genomes indicate different ecological drivers of diversification among Bacillus cereus clades. Issue 13 (17th May 2022) - White, Hugh; Vos, Michiel; Sheppard, Samuel K.; Pascoe, Ben; Raymond, Ben
Abstract: Bacterial clades are often ecologically distinct, despite extensive horizontal gene transfer (HGT). How selection works on different parts of bacterial pan‐genomes to drive and maintain the emergence of clades is unclear. Focusing on the three largest clades in the diverse and well‐studied Bacillus cereus sensu lato group, we identified clade‐specific core genes (present in all clade members) and then used clade‐specific allelic diversity to identify genes under purifying and diversifying selection. Clade‐specific accessory genes (present in a subset of strains within a clade) were characterized as being under selection using presence/absence in specific clades. Gene ontology analyses of genes under selection revealed that different gene functions were enriched in different clades. Furthermore, some gene functions were enriched only amongst clade‐specific core or accessory genomes. Genes under purifying selection were often clade‐specific, while genes under diversifying selection showed signs of frequent HGT. These patterns are consistent with different selection pressures acting on both the core and the accessory genomes of different clades and can lead to ecological divergence in both cases. Examining variation in allelic diversity allows us to uncover genes under clade‐specific selection, allowing ready identification of strains and their ecological niche.